Asymmetric resistive switching processes in W:AlOx/WOy bilayer devices. (27th March 2015) - Wu 吴, Hua-Qiang 华强; Wu 吴, Ming-Hao 明昊; Li 李, Xin-Yi 辛毅; Bai 白, Yue 越; Deng 邓, Ning 宁; Yu 余, Zhi-Ping 志平; Qian 钱, He 鹤
Abstract: Asymmetric resistive switching processes were observed in W:AlO x /WO y bilayer RRAM devices. During pulse programming measurements, the RESET speed is in the range of hundreds of microseconds under −1.1 V bias, while the SET speed is in the range of tens of nanoseconds under 1.2 V bias. Electrical measurements with different pulse conditions and different temperatures were carried out to understand these significant differences in switching time. A redox reaction model in the W:AlO x /WO y device structure is proposed to explain this switching time difference.